PENGEMBANGAN LKS DENGAN PENDEKATAN MULTIKULTURAL PADA PEMBELAJARAN SENI BUDAYA DAN KETERAMPILAN DI SEKOLAH DASAR - Zariul Antosa; Muhammad Fendrik; Roza Helfianti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is a development research, conducted to develop Student Worksheet (LKS) with multiculturalbased. LKS is designed by integrating various forms of cultural diversity of students into subjects of CulturalArts and Skills. This study aims to introduce and grow regional cultural values to elementary school students.This LKS was developed using 4-D model consisting of four stages namely define, design, develop, anddisseminate. The instruments used in the study consisted of validation questionnaires, pretest posttest andstudent response questionnaires. LKS that has been designed validated by 3 people namely learning materialexperts, media experts, linguists, and teachers of class V. After the design of LKS validated and then tested onthe students of Class V SDN 11 Rice. The result of the research shows that LKS based on multicultural that hasbeen designed is declared very feasible by the validator with score percentage 86,74. In the limited trial stage, apretest average score of 46.54 and posttest of 65.35 was obtained. For N-Gain results in pretest and posttest is0.33, with medium category. Student response to LKS based multicultural is in very good category with scorepercentage 92,16. In dissemination stage (product disseminate) on Class VI obtained response equal to 85,32with very good category. For teacher response obtained an average of 90.1 with very decent category.